The role of foliar endophytes in modulating southern corn rust severity: implications for biocontrol strategies - Yang, Lujia; Li, Lili; Song, Yingying; Zhang, Yongsheng; Yang, Jie; Cui, Hongying; Guo, Wenxiu; Lv, Suhong; Men, Xingyuan (Frontiers in Plant Science, 2025)
Southern corn rust (SCR), caused by Puccinia polysora, is a major foliar disease that threatens global maize production. Current SCR management strategies prioritize genetic resistance and chemical control, but how foliar endophytic fungal communities modulate host susceptibility to P. polysora remains poorly understood. In this study, we profiled the endophytic communities in P. polysora-infected and non-infected maize leaves across 14 geographically distinct regions in eastern China. Our results revealed that P. polysora infection significantly altered the foliar endophytic community, with infected leaves exhibiting higher operational taxonomic unit (OTU) richness (722 vs. 572 OTUs) while reducing community evenness. Diversity metrics were significantly altered, with significant reductions in Shannon diversity and Chao1 index values for non-infected states. Network analysis revealed that infection caused a notable reduction in microbial connectivity and complexity, particularly in low- and medium-susceptibility regions, where positive intertaxon associations declined by 42.6% and 35.3%, respectively. High-susceptibility region networks retained greater stability, suggesting differential microbial resilience under pathogen pressure. Redundancy analysis further demonstrated that temperature was the dominant environmental factor shaping microbial assemblages, especially under infection conditions. Notably, correlation analysis further revealed that Alternaria was positively associated with host resistance (r = 0.37, p = 0.05), underscoring its potential role in enhancing resistance to P. polysora. Conversely, Dioszegia and Naganishia were negatively correlated with resistance (r = −0.36, p = 0.056; and r = −0.34, p = 0.074, respectively), implying potential roles in facilitating infection. This study reveals key mechanistic links between foliar endophytic communities and SCR infection, providing a basis for sustainable biocontrol interventions in maize.